The genome assembly and annotation of the Oriental rat snake Ptyas mucosa - Jiangang Wang; Shiqing Wang; Song Huang; Qing Wang; Tianming Lan; Ming Jiang; Haitao Wu; Yuxiang Yuan (GigaByte, 2023)
The Oriental rat snake Ptyas mucosa is a common non-venomous snake of the colubrid family, spanning most of South and Southeast Asia. P. mucosa is widely bred for its uses in traditional medicine, scientific research, and handicrafts. Therefore, genome resources of P. mucosa could play an important role in the efficacy of traditional medicine and the analysis of the living environment of this species. Here, we present a highly continuous P. mucosa genome with a size of 1.74 Gb. Its scaffold N50 length is 9.57 Mb, and the maximal scaffold length is 78.3 Mb. Its CG content is 37.9%, and its gene integrity reaches 86.6%. Assembled using long-reads, the total length of the repeat sequences in the genome reaches 735 Mb, and its repeat content is 42.19%. Finally, 24,869 functional genes were annotated in this genome. This study may assist in understanding P. mucosa and supporting medicinal research.